Internationalization Issues in Chinese Firms: One Belt, One Road-Based Perspective - Wu, Xia (Frontiers in Psychology, 2022)
The underlying aim of this study was to investigate the impact of HRM practices, Organizational identity and Brand leadership on Employee brand-based equity through mediatory role of Brand knowledge dissemination. A questionnaire was adopted to obtain data from 421 employees working in the construction sector of China. The Smart-PLS software was used to analyze the data through the help of a structural equation modeling (SEM) technique. The results revealed that HRM practices, Organizational identity had a positive and significant relationship with Employee brand-based equity. While brand leadership had no direct impact on Employee brand-based equity. The results also revealed that brand knowledge dissemination mediated the relationship between Independent variables (HRM practices, organizational identity and brand leadership) and dependent variable Employee brand-based equity. Theoretically, this paper made a valuable contribution by examining the impact of HRM practices, organizational identity and brand leadership on Employee brand-based equity. In terms of practical implications, this study would obviously help the organizations to improve their employee brand-based equity through HRM practices and organizational identity.